Perceived and preferred teaching styles (methods) of English for Specific Purposes (ESP) students - Norzila Abdul Razak,; Fauziah Ahmad,; Parilah Mohd Shah, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This study aims to identify the dominant teaching styles of the English Language lecturers as perceived by the students. This study also investigates the perception and preference of the students with respect to their English language lecturers’ teaching styles. Comparisons were made between (i) male and female students’ perceptions with respect to their lecturers’ teaching styles (ii) male and female students’ preferences with respect to their lecturers’ teaching styles and (iii) the students’ perceptions and preferences with respect to their lecturers’ teaching styles. The teaching styles mentioned are based upon Grasha’s Model (1996) consisting of Expert style, Formal Authority style, Personal Model style, Facilitator style and Delegator style. This study is a survey method using 5-point Likert Scale questionnaire as the instrument to collect data. The data collected was analysed using SPSS version 13.0. Simple random sampling was employed in this study. The samples were 175 semester 5 students from the three Engineering Departments of Sultan Salahuddin Abdul Aziz Shah Polytechnic, Shah Alam, Selangor. Descriptive ststistics such as frequency, percentage, mean and deviation were used to describe the respondents’ profile and, perceptions and preferences with respect to their lecturers’ teaching styles. Meanwhile, t-tests were used to analyse the differences between (i) gender with respect to the lecturers’ teaching styles, and (ii) perceived and preferred teaching styles. The results of the study showed that the three most dominant teaching styles of the lecturers perceived by the students were Expert, followed by Personal Model and then Delegator. It was also found that the students’ most preferred teaching style was Facilitator style while Formal Authority style being the least preferred. In terms of gender, there was no significant difference in perceptions as well as preferences between the male and female students in any of the mean scores of all teaching styles. The students’ perceptions and preferences differed significantly in all teaching styles of the Grasha’s Model (1996) except for Expert teaching style. The results demonstrated statistically significant higher scores in terms of preferences to Formal Authority, Personal Model, Facilitator and Delegator styles. There was no significant difference between the students’ perceptions as well as preferences for Expert teaching style